Analisa Strategi Pemasaran untuk Meningkatkan Penjualan Produk Telur pada BUMDES Mekarsari - Purbasari, Evi; Asnawi, Anita; Lestari, Damajanti Sri; Priyanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze marketing strategies that can be implemented by BUMDes Mekar Sari to increase the sales of local chicken eggs. BUMDes Mekar Sari is a village-owned enterprise located in Sabron Sari, Sentani Barat District, facing challenges in distribution, marketing, and operational efficiency. This research employs a descriptive qualitative method with a case study approach, where data were collected through observation, in-depth interviews, documentation, and consumer questionnaires. The analysis tools used include SWOT analysis, Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, and Strategic Position and Action Evaluation (SPACE) Matrix. The results indicate that BUMDes Mekar Sari possesses significant internal strengths such as high-quality products, a strategic location, and a relatively high profit margin. However, weaknesses such as limited distribution capacity, high employee turnover, and underutilized digital marketing strategies remain obstacles that need to be addressed. Based on the IFE and EFE Matrix scores of 2.44 and 2.68, respectively, and the SPACE Matrix positioning in the Aggressive quadrant, an expansive marketing strategy is recommended, focusing on strengthening distribution networks, optimizing digital marketing, increasing production capacity, and implementing customer loyalty programs. A one-year action plan has been formulated as an implementation step to achieve sustainable sales growth.